Julian of Norwich’s a Revelation of Love: A Grounded Cognition Approach to a Late Medieval Text - Katarzyna Stadnik (Research in Language)
Julian of Norwich was a late medieval anchoress and writer, whose work, The Showings, is known for its vivid imagery and bodily resonance it prompts in the reader. The paper identifies a gap in research on the embodied aspects of Julian’s imagery. The article discusses the connection between perception, action and the grounded nature of cognition, exploring its role in structuring Julian’s text. It uses the conceptions of situated conceptualisation and sociocultural situatedness to embed the work in the visual/material culture of the Middle Ages. It reveals how the mystic construes emotionally intense images, which underpin the abstract language of the text’s final chapters. To conclude, the recent conceptions from cognitive science may expand the analytical toolkit of cognitive-diachronic research in particular, helping illuminate the interplay of language, culture, and cognition.